Microsphere – the future of optical microscopes: Beating the diffraction limit with microsphere‐assisted technology. Issue 3 (16th June 2021) - Chen, Lianwei; Zhou, Yan; Zhou, Rui; Hong, Ming Hui
Abstract: The diffraction limit has always been a fundamental barrier in optical science and engineering. It limits the minimum feature size in surface patterning technologies such as lithography and laser direct writing. It also restricts the resolution for optical imaging.